Fragmentação da metrópole: constituição da Região Metropolitana de Goiânia e suas implicações no espaço intraurbano de Aparecida de Goiânia - Pinto, José Vandério Cirqueira (2009)
A common phenomenon occurred in the most of Brazilian cities is related to urban expansion without space planning. The municipalities located in the Brazilian metropolitan areas, receiving large number of people and exercising ineffective public policies of space organization, they have the growth accelarated and they acquire Sharp urban problemas. This way, a lot of municipalities of the suburb apper around of the metropolis. The municipalities have little basic sutruture and they have little centers of of consumption and job. This condition make dependence of the municipalities with relation to metropolis. Aparecida de Goiânia is a typical exemple of Braziliam municipality of the suburb. This municipality is located in the metropolitan area of Goiânia. The municipality is having deep transformations in the urban struture. This way, the objective of this work is to develop a reflexion about this recent transformations occurred in the urban space of Aparecida de Goiânia. The methodology used was the proposal to divide the history of the municipality in periods to investigate the urban development that occurred since the origin of ghe municipality until the present. With basis in the proposal of periodization, this work propose to clarify the metamorphoses that the city had in a short period. The city appeared in the rural interior of Goiás, in 1922,, through religious expressions and through political interests of place. Between 1970 and 1980, Aparecida de Goiânia got accelerate urban growth, connected to suburbanization of Goiânia. Currently, Aparecida de Goiânia hás a dynamic economic articulation, with urban structure fragmented, multiple and unfair, it is characterized by new centers, specalized áreas and social problems. With basis in the informations adn in the discussion of the phenomena that transformed the urban structure of Aparecida de Goiânia, it had like result the notion of that Aparecida de Goiânia change the condiction of dependence of Goiânia where it is grouped, changing the space relations with the metropolitan area of Goiânia. Before, the space relations of Aparecida with Goiânia were exercised of strict way, but currently it develop na interaction of supplement base don the Exchange multiple and complex.